Preparation and Characterisation of Photoactive Supramolecular Soft Materials - Smith, Shaun (2024)
Soft material systems containing photosensitizers have been prepared and studied both for their use as photodynamic therapy agents and to investigate single molecule diffusion phenomena at the microscale. Gemini imidazolium amphiphiles were used to prepare supramolecular gels that possessed a liquid phase containing various ratios of water and ethanol. Photoactive compounds such as phthalocyanines and porphyrins were incorporated into the gels during preparation to yield a photoactive supramolecular material. Partly, this work outlines an investigation into the aggregation and fluorescence properties of these photoactive compounds both in solution and as part of the gel material as relates to their ability to generate singlet oxygen for antimicrobial photodynamic therapy, where significant enhancement of singlet oxygen generation of a water-soluble phthalocyanine was measured. Further, investigation into the molecular diffusion characteristics of these photoactive compounds confined to gel fibres was conducted using total internal reflection fluorescence microscopy and the results were statistically analysed. Changes in photon flux and the protonation state of a phthalocyanine altered its movement, as measured by mean instantaneous velocity calculations and mean square displacement analysis. This study provides important insights into the fundamental mechanism of molecular diffusion in gels and may have practical implications in the development of novel materials for optoelectronic and sensing applications. Glycopolymers containing a repeating unit of a modified galactose ring were also incorporated with the gel to form a gelator-glycopolymer hybrid hydrogel. A disruption of gel morphology brought about by increasing glycopolymer concentration was seen as analysed through electron and fluorescence microscopy. Confocal fluorescence microscopy of the imidazolium gels containing a range of fluorophores was attempted to correlate with total internal reflection fluorescence microscopy, along with a study of the dynamics of diketopyrrolopyrrole derivatives. Migratory behaviour of these diketopyrrolopyrrole compounds from outside to within the fibre was observed and studied. Finally, cryogenic scanning electron microscopy was employed to potentially correlate the gel morphology observed both in the dried state as seen with conventional scanning electron microscopy and in the hydrated state as seen with fluorescence microscopy. In cryogenically frozen imidazolium gels containing diketopyrrolopyrrole derivatives, thinner fibre widths were observed. In a concentration study, fibre width increased when moving from zero to 100 μM of zinc phthalocyanine tetrasulfonic acid within the cryogenically frozen gel but increasing the concentration to 500 μM had no further effect on fibre width. This is different from conventional SEM imaging of dried fibres, where increasing zinc phthalocyanine tetrasulfonic acid concentration from 100 μM to 500 μM led to significant changes in gel morphology, making the fibres no longer visible. The studies of the imidazolium gels reported in this work could contribute to potential applications in photodynamic therapy and provide further important foundational information about photoactive soft materials.